Regeneración del Frente Urbano del Malecón del río Magdalena de la ciudad de Neiva (2023)
In the Magdalena river boardwalk in the city of Neiva, over the years, urban deterioration has increased due to the neglect of government entities in various aspects such as the requirement of land uses located parallel to the boardwalk which are not suitable and do not agree with the POT of the city, which has led to increased insecurity, dirt, invasion of public space by street dwellers and that this is unattractive. Therefore, the objective of this research is to recognize the causes that encourage the deterioration and underutilization of this ecotourism trail, taking into account the activities that occur in the environment in which it is located.